PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE LEARNING CYCLE 7E TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII SMPN 1 LUBUK SIKAPING TAHUN PELAJARAN 2021/2022 - Chyntia Ersa Putri (Jurnal Edukasi dan Penelitian Matematika, 2022)
This study aims to determine whether the understanding of mathematical concepts of students whose learning applies the 7E Learning Cycle model is better than the understanding of mathematical concepts of students whose learning applies direct learning models in class VII SMPN 1 Lubuk Sikaping. The type of research is a quasi-experimental with Static Group Design. The population of this study was students in grades VII.1 to VII.10 of SMPN 1 Lubuk Sikaping who were registered in the 2020/2021 academic year. The research instrument is the final test which is analyzed using a hypothesis test, namely the U Mann Whitney test. Based on the statistical test analysis, it was obtained that the P-value was 0.0001, where the P-value was smaller than the real level of 0.05, which means that H0 is rejected. This shows that the Learning Cycle 7E learning model has an effect on understanding the mathematical concepts of students in class VII SMPN 1 Lubuk Sikaping.Keywords– Learning Cycle 7E, Pembelajaran Langsung, Pemahaman Konsep Matematis